2016
DOI: 10.24246/agric.2014.v26.i1.p12-19
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Biaya Dan Pendapatan Usahatani Padi Di Kabupaten Karanganyar

Abstract: PENDAHULUANUsahatani adalah suatu kegiatan mengusahakan dan mengkoordinir faktor-faktor produksi berupa lahan, tenaga kerja, dan modal sehingga memberikan manfaat sebaik-baiknya. Usahatani merupakan cara-cara menentukan, mengorganisasikan, dan mengkoordinasi penggunaan factorfaktor produksi seefektif dan seefisien mungkin sehingga usaha tersebut memberikan pendapatan semaksimal mungkin (Suratiyah, 2008).Usaha di sektor petanian dibedakan menjadi 5 sub sektor yaitu sub sektor tanaman bahan pangan, perkebunan, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
3
9
0
11
Order By: Relevance
“…This means that rainfed rice farming is the main source that contributes to household income compared to other businesses. For farmers, rice farming plays a role in providing staple food and a source of household income for farmers (Barokah et al, 2014). The main activities and main source of income for the community, especially people in rural areas, still depend on the agricultural sector.…”
Section: The Contribution To Household Incomementioning
confidence: 99%
“…This means that rainfed rice farming is the main source that contributes to household income compared to other businesses. For farmers, rice farming plays a role in providing staple food and a source of household income for farmers (Barokah et al, 2014). The main activities and main source of income for the community, especially people in rural areas, still depend on the agricultural sector.…”
Section: The Contribution To Household Incomementioning
confidence: 99%
“…When comparing before and after farmers developed cacao-based agroforestry, there was a significant increase in land productivity. Before cacao-based Agroforestry development, the land was only planted with rice and/or secondary crops in monoculture with an average annual income of IDR 7,286,671,-or US$ 613.44/ha (Barokah et al, 2014), while after cacao-based agroforestry development, the generated income was IDR 16,307,723,-or equal to US$ 1,174.69/ha/year. Notaro et al (2020) reported that the option for crop species and planting density in cacao agroforestry systems impacted the quantity and the economic value of the agricultural products sold and consumed by producers.…”
Section: Cacao Productionmentioning
confidence: 99%
“…Biaya produksi variabel per musim usahatani kedelai berdasarkan data pada tabel 7 sebesar Rp1.101.500/lahan garapan (0,69 hektar) atau setara dengan nilai Rp1.748.550,72/ hektar. Total Biaya ini masih lebih rendah jika dibandingkan dengan biaya usahatani di Kabupaten Sukoharjo yang mencapai Rp 3.947.131,58 per hektar (Barokah, 2011). Biaya untuk pembelian benih kedelai merupakan biaya variabel terbanyak yakni mencapai 50,16 %.…”
Section: Identifikasi Dan Analisis Ketersediaan Tenaga Kerja Dalam Keluargaunclassified